Artificial inseminator service provider: Recording booklet on service provision - International Livestock Research Institute (International Livestock Research Institute, 2024)
This booklet is to keep records related to artificial insemination (AI) service provision. Records kept include those on clients, animals, and AI related activities. Fill one double-spread age for each round of artificial insemination. This includes heat detection or synchronization, the artificial inseminations (including all repeats), pregnancy detection, and resultant farrowing / calving details. The data collected is intended to be used to (a) improve service provision – you can keep track of when next services are due and contact the client; (b) improve outcomes AI outcomes by allowing you to examine AI success rates and factors affecting these.